Epidemiological profile and health indicators of taxi drivers in the city of João Pessoa, Paraiba: a pilot study (Research, Society and Development, 2022)
Introduction: The osteomyoarticular disorders are one of the biggest public health problems nowadays, due to their high prevalence, representing one of the main problems among workers, impacting negatively on their quality of life, which can lead to absenteeism and early disability. In this case, the transportation worker, particularly taxi drivers, who face a stressful routine due to weather-related inclement weather, traffic conditions and urban roadways, as well as excessive work hours, making them vulnerable to musculoskeletal disorders. Objective: To establish the epidemiological profile of taxi drivers in the city of João Pessoa-PB, in addition to identify the factors related to pain and work activity. Methods: This was a descriptive, cross-sectional, retrospective, epidemiological, population-based study with 27 taxi drivers. The data was analyzed, using the statistical program Statistical Packaget Social Science, version 20.0 for Windows. Results: Of the 27 taxi drivers studied, all were male, with a mean age of 50.5 years, and reported having some type of comorbidity. About 48.1% of the workers reported pain. Regarding the site of pain, the main region mentioned was the spine, with the lumbar region being the most affected, followed by the cervical region. Conclusions: The alarming prevalence of musculoskeletal symptoms among taxi drivers suggests the need for programs aimed at the health of these workers in the workplace.